O Brasil em 2035: Tendências e incertezas para a área social - Yacine Guellati; Claudio Dantas Monteiro; Almir de Oliveira Júnior (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– In Brazil, it has been difficult to elaborate governmental planning surpassing the four-year spectrum from the Pluriannual Plans. Despite the fact of long-term planning attracting a wide range of sectors, it still occupies a small space in both political and State agendas. Hence, the present study intends to initiate a new cycle of debates regarding the issue as it presents questions and factors to subsidy long-term strategies. Using methodological tools from Strategic Prospective, we present trends and uncertainties regarding social problems in the Brazilian case - contemplating topics such as demographic changes, inequalities, urban and social infrastructure, years of schooling of the population and the use of technology in education. This study is part of Brazil 2035, a project whose objective is to provide subsidies to formulate long-term development strategies for Brazil through Prospective Scenarios. Thus, this text presents a preliminary stage of a prospective process regarding the identification and analysis of the main variables. We do not intend to be conclusive; but rather to present some key factors and questions, which will affect Brazilian development until 2035.
Keywords: I00; J10; J11; L38; O18; 330; strategic prospective; prospective scenarios; long-term planning; society; public policy; demographic changes; urban and social infrastructure; education and culture